DEVELOPMENT OF THE MODERN UZBEK POETRY LANGUAGE - Abduraxmonova Irodaxon Shuhratjon qizi (Web of Journals Publishing, 2025)
This article covers the historical development of the lexicon of Uzbek poetry, its main lexical sources and poetic language features. The lexicon of Uzbek poetry in the process of its formation borrowed words from Turkish, Persian-Tajik and Arabic languages, undergoing phonetic and morphological changes. Unlike the traditional classical Uzbek poetic language, the modern Uzbek poetic language is distinguished by its rich Turkish word base.
Keywords: Poetic lexicon, imagery, expressiveness, prosaic speech, synonymy, classical and modern poetic language.